2013
DOI: 10.1016/j.uclim.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the urban cooling effects of an intensive green roof due to vegetation damage

Abstract: Green roofs are increasingly being utilised as urban climate adaptation measures given good evidence of their passive cooling effects. Shading of conventional building surfaces, higher albedo and latent cooling from evapotranspiration mean that vegetated surfaces can be used to significantly lower surface and air temperatures in cities. The extent to which cooling properties may be affected by poor maintenance, green roof damage and the general health of the vegetation is not as well known. This study investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 41 publications
2
34
0
6
Order By: Relevance
“…The cooling effects were more pronounced in summer than spring and fall, on sunny days than rainy and cloudy days, and in nighttime than daytime. The result of higher nocturnal cooling effects is consistent with Speak et al's study, which also found that across a day strongest cooling occurs at night [38]. However, the effects were mostly restricted to limited distance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The cooling effects were more pronounced in summer than spring and fall, on sunny days than rainy and cloudy days, and in nighttime than daytime. The result of higher nocturnal cooling effects is consistent with Speak et al's study, which also found that across a day strongest cooling occurs at night [38]. However, the effects were mostly restricted to limited distance.…”
Section: Discussionsupporting
confidence: 89%
“…Evaluation of the temporal variations of green-roof thermal performance with respect to weather effects enables a deep and comprehensive understanding of its role as a UHI mitigation measure. Speak et al [38] compared the seasonal and diurnal cooling effects between a healthy green roof and another damaged green roof with exposed bare substrate. Results found that both green roofs display remarkable temporal variations in cooling effects.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation in IES-VE is limited to conductive heat exchange through the roof as well as the available construction materials in IES-VE. It does not account for air temperature cooling due to evapotranspiration that can take place within a height of 1-2 m above the green roof [65].…”
Section: Discussionmentioning
confidence: 99%
“…Stressed, unhealthy or declining vegetation cover will also cause reduced ecosystem function. Speak et al (2013) showed that green roofs can lower the air temperature above the system with approximately 1 °C. The effect was increased at night by 50% coinciding with the time when UHI is the strongest.…”
Section: Selection and Management Of Urban Vegetation Under Changing mentioning
confidence: 99%